ICT and innovation in teaching learning methods in higher education - Sengupta, Enakshi; Blessinger, Patrick (Emerald Publishing Limited, 2022)
The role of ICT is now central to the quality of classroom delivery, supporting the growth of research and expanding horizons for students with limited accessibility to education. But what impediments exist surrounding ICT in Higher Education? How can we overcome the inaccessibility, economic disparity, and ineffective implementation which have prevented the efficient adoption, diffusion and integration of ICT into pedagogy? ICT and Innovation in Teaching Learning Methods in Higher Education is a collection of interventions and collaborative practices from across the world that showcase the multifaceted ways of how various institutions have been engaged in supporting teaching and learning with the use of technology. Written at a critical moment of evolution for higher education, the chapters explore how ICT has created a positive impact in the teaching-learning environment and how it is equipping our future generation with the skills required to face a changing job market, but also present the challenges and solutions to enabling access to ICT resources across educational settings.
Includes index.
Keywords: Education, Higher -- Effect of technological innovations on.; Education, Higher -- Data processing.; elektronické knihy; Electronic books.; Education -- Computers & Technology.; Higher & further education, tertiary education.; electronic books